The efficacy and safety of anlotinib for subsequent line treatment of small cell lung cancer: a systematic review and meta-analysis. Issue 2 (April 2023) - Xu, Huilin; Cao, Dedong; Jie, Fangfang; He, Anbing; Ge, Wei
Background: Anlotinib is one of the tyrosine kinase inhibitors that exhibits promising anti-tumor effect in several cancers. However, the efficacy and safety of anlotinib in pre-treated small cell lung cancer (SCLC) is not well determined. Herein, we performed this meta-analysis to summarize the effectiveness and safety of anlotinib in the treatment of pre-treated SCLC. Methods: The databases, such as PubMed and Embase, were searched to identify eligible studies. Clinical studies reporting the efficacy and safety of anlotinib in the treatment of patients with pre-treated SCLC were included. The main endpoints were overall survival (OS), progression-free survival (PFS), overall response rate (ORR), disease control rate (DCR), and adverse events. The Review Manager 5.4 and STATA 14 statistical software were used to perform the meta-analysis. Results: A total of 13 studies were included, involving 779 patients with SCLC. The ORR and DCR for the anlotinib group were 0.21 (95%CI: 0.12- 0.31; p < 0.01) and 0.76 (95%CI: 0.69- 0.83; p < 0.01), respectively. The summarized PFS and OS for the anlotinib group were 3.46 (95%CI: 2.68-4.24), and 6.86 (95%CI: 5.79-7.93) months, respectively. Compared with control group, the PFS in the anlotinib group was significantly longer standard mean difference(SMD)=0.76, 95%CI: 0.11, 1.41; p = 0.02). In terms of safety, the most common grade 3 or higher adverse events in the anlotinib group were hypertension (9%; 95%CI: 6%-13%), hand-foot syndrome (6%; 95%CI: 2%-9%), and fatigue (4%; 95%CI: 2%-7%). Conclusions: Anlotinib may be associated with favorable efficacy outcomes in pre-treated SCLC patients with acceptable safety.